How teachers respond to students' mistakes in lessons: A cross-cultural analysis of a mathematics lesson. Issue 3 (10th July 2017) - Sarkar Arani, Mohammad Reza; Shibata, Yoshiaki; Sakamoto, Masanobu; Iksan, Zanaton; Amirullah, Aini Haziah; Lander, Bruce
Abstract : Purpose: The purpose of this paper is to capitalize on the advantages of an evidence-based lesson analysis while proposing a method of research on teaching that offers opportunities for deeper reflections. The objective is to examine how well a transnational learning project such as this one can determine the cultural script of a mathematics lesson in Malaysia through the perspective of Japanese educators well trained in the lesson study approach. Emphasis here is on a cross-cultural analysis to view in depth the cultural script of teaching mathematics in Malaysia with particular focus on how teachers respond to students' mistakes in a mathematics lesson. Design/methodology/approach: This paper draws on data collected by the authors in a lesson study in Malaysia that aimed to provide a cross-cultural analysis of a Malaysian mathematics lesson (grade 10) through the eyes of Japanese educators. Data retrieved should determine the cultural script of a mathematics class in Malaysia with an emphasis on Malaysian teachers' responses to students' mistakes in class. The cross-cultural analysis of a lesson is a comparative method that reveals the hidden factors at play by increasing awareness of characteristics in classroom situations that are self-evident to all involved members. Findings: The findings are intended to the cultural script of Malaysia in the context of "classroom culture regarding mistakes" and "mistake management behavior." The impact on the quality of teaching and learning also discussed in relation to how it can be improved in practice from the following perspectives: the teacher's attitudes toward student mistakes; how mistakes are treated and dealt with in class; and how learning from mistakes is managed. The data inTable II provide a meta-analysis of evidences of "classroom culture regarding mistakes" and "mistake management behavior" of the teacher from the Malaysian researchers and practitioners' perspective as well as from the lens of the Japanese educators. Research limitations/implications: This study realizes that both sets of research studies value the importance of mistakes. It is important to identify the source of students' mistakes and further learn from them. In order to reveal the overall structure of the cultural script of lessons, we need to realize that various cultural scripts are at work in the production of any given lesson. In the future, the authors hope to develop the potential of this view of culture script of teaching through cross-cultural analysis for lesson study and curriculum research and development. Practical implications: This study aims to capitalize on the advantages of evidence-based lesson analysis through the lesson study process while proposing a method of research on teaching that offers opportunities for deeper reflections. The objective is to examine how well a transnational learning project such as this one can determine the cultural script of a mathematics lesson in Malaysia through the perspective of Japanese educators well trained in the lesson study methodology. Social implications: The authors need to obtain reflective feedback based on concrete facts, and for this reason "lesson study, " a pedagogical approach with its origins in Japan, is attracting global attention from around the world. This study focuses on the discrete nature, the progression, significance, and the context of lessons. That is, by avoiding excessive abstraction and generalization, reflection based on concrete facts and dialogue retrieved from class observations can be beneficial in the process. The mutual and transnational learning between teachers that occurs during the lesson study process can foster the building and sharing of knowledge in teaching practice. Originality/value: There is currently little empirical research addressing "classroom culture regarding mistakes" which mostly represents how teachers and students learn from mistakes in the classroom. This study focuses on a cross-cultural analysis to view in depth the cultural script of teaching mathematics in Malaysia with particular focus on how teachers respond to students' mistakes in a mathematics lesson. The following perspectives are examined: the teacher's attitudes toward student mistakes; how mistakes are treated and dealt with in class; and how learning from mistakes is managed.